Juridical Review on the Support of Inheritance Rights in the Perspective of Compilation of Islamic Law - Andri, Muhammad; Nur Fareha (Faculty of Law, Universitas Pekalongan, 2024)
The inheritance system applies to Indonesian citizens. In addition to the legal system of Islamic inheritance, there is also a civil and customary legal system. The problem of inheritance in particular concerning the substitute heir becomes a subject of interesting discussion when viewed from a normative point of view. this study tries to study how the position of substitute inheritors in the compilation of Islamic law. as well as how the legal protection for the replacement heir in accordance with Islamic compilations of law. Normative jurisprudential research method in this penalty prioritizes library materials, court decisions that have been incrachted, or documents called secondary data. Primary, secondary and tertiary laws consist of primary, secundary, and tertiair materials, and these methods are used to conduct this research. Rules in Islamic inheritance law and rulings of the courts that have already incracht used as the basis for this method. research results show that: The legal position concerning a substitute inheritor in the Islamic heritage in Indonesia is formulated provisionally in article 185 paragraph 1, that is, the heir who died before the heirs and can be replaced by his children, except those mentioned in article 173. (melakukan tindakan penganiayaan berat). The inheritance acquired by the substitute heir is not always the same as that replaced, i.e. it is not permitted to add from the acquisition of the equivalent heir to the replaced but may reduce it. The substitution referred to in Article 185 covers the replacement of place, degrees, and unlimited rights between men and women as heirs, i.e. regulating the substitution of place when a nephew or grandson takes the role of a parent as a brother-in-law or otherwise. According to the provisions of the article, an heir who died before the heir is considered to be a replaced heir, and also must not exceed the share of the inheritance rights of the sederajad so that the compilation of Islamic law in article 185 (2) gives a maximum limit of one-third for the replacement heir.